Desmoid tumor in the male breast refractory to systemic treatment: case report - Luiza de Lima Rodrigues, Celia; Quaranta Damião, Soraia; Maria Alves Soares, Cândida; Miranda Lago, Bianca; Alves de Souza, Juliana; Graziano, Luciana; Souza Guatelli, Camila; Galvão Vieira Bitencourt, Almir (Mastology, 2025)
Desmoid-type fibromatosis, an intermediate soft tissue tumor known for its local infiltrative behavior and high recurrence rate, is uncommon in the male breast. The report outlines the clinical journey of a 44-year-old male presenting with a rapidly growing breast mass, initially managed with a watchful waiting approach and subsequent systemic therapies including celecoxib, sorafenib, and a combination of methotrexate and vinblastine, all of which proved ineffective. Genetic testing revealed a catenin beta 1 (CTNNB1) mutation, indicative of a sporadic tumor. Despite various treatment attempts, significant tumor progression was observed, necessitating surgical intervention followed by radiotherapy. This case underscores the challenges in managing desmoid tumors, emphasizing the importance of multidisciplinary approaches and the potential need for surgical resection when conventional therapies fail.